STRATEGIC LEADERSHIP AND NATIONAL SECURITY IN A TIME OF GLOBAL GEOPOLITICAL CRISIS: MAQASID AL-SHARI'AH'S PERSPECTIVE ON INDONESIA UNDER PRESIDENT PRABOWO SUBIANTO - Rahman Fanani; Moch. Nurcholis; Mowafg Masuwd (Universitas Kiai Abdullah Faqih Gresik, 2026)
The inauguration of Prabowo Subianto as the President of Indonesia marks a significant shift in the nation’s foreign and defense policy toward